MALDI-target integrated platform for affinity-captured protein digestion - Ahmad Tajudin, Asilah; Adler, Belinda; Ekstrom, Simon; Marko-Varga, Gyorgy; Malm, Johan; Lilja, Hans; Laurell, Thomas (Elsevier, 2014)
To address immunocapture of proteins in large cohorts of clinical samples high throughput sample processing is required. Here a method using the proteomic sample platform, ISET (integrated selective enrichment target) that integrates highly specific immunoaffinity capture of protein biomarker, digestion and sample cleanup with a direct interface to mass spectrometry is presented. The robustness of the on-ISET protein digestion protocol was validated by MALDI MS analysis of model proteins, ranging from 40 fmol to 1 pmol per nanovial. On-ISET digestion and MALDI MS/MS analysis of immunoaffinity captured disease-associated biomarker PSA (prostate specific antigen) from human seminal plasma are presented.